Letter from Carl D. Duncan to Patricia Whiting, October, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan recounts a lecture he recently attended in which Dr. Jack Shelton discussed the effects and uses of L.S.D.